Rehabilitation for People Living with Dementia: A Scoping Review of Processes and Outcomes - Maiken B. Ravn; Kirsten S. Petersen; Jette Thuesen (Journal of Aging Research)
Objectives. The aim of this scoping review was to map intervention studies of rehabilitation for people living with dementia regarding processes and outcomes, with a particular focus on whether the intervention is person-centred, home-based, or organised adopting a multidisciplinary approach and measures outcomes relating to everyday functioning and well-being. Methods. A systematic search of electronic databases was conducted in PubMed, CINAHL, PsycINFO, Embase, and Cochrane. Studies from 2005 to November 2018 were collected and screened for relevance and quality. Randomised control trials and prospective cohort trials reporting a statistically significant effect on one or more outcome measures were included. Included studies were mapped according to selected processes and outcome measures. Results. Twenty-six intervention studies were included and mapped. Nineteen of the interventions were person-centred, nine were home-based, and 14 reported a multidisciplinary approach. Twelve of the interventions had activities of daily living as an outcome measure, and 14 had quality of life as an outcome measure. Conclusion. Person-centredness appears in most rehabilitation interventions for people living with dementia. Other processes and outcomes are heterogeneously described in the research literature. Rehabilitation programmes can be home-based or take place at a centre. Although not exclusive, the organisation of rehabilitation can be multidisciplinary. Fewer than half of the intervention studies measure the impact on activities of daily living and quality of life. Future guidelines must take into account the weak evidence regarding these aspects.